Hesperidin, a citrus bioflavonoid, decreases the oxidative stress produced by carbon tetrachloride in rat liver and kidney - Tirkey, Naveen (BioMed Central, 2005)
BACKGROUND: CCl(4 )is a well-established hepatotoxin inducing liver injury by producing free radicals. Exposure to CCl(4 )also induces acute and chronic renal injuries. The present study was designed to establish the protective effect of hesperidin (HDN), a citrus bioflavonoid, on CCl(4)-induced oxidative stress and resultant dysfunction of rat liver and kidney. METHODS: Animals were pretreated with HDN (100 and 200 mg/kg orally) for one week and then challenged with CCl(4 )(2 ml/kg/s.c.) in olive oil. Rats were sacrificed by carotid bleeding under ether anesthesia. Liver enzymes, urea and creatinine were estimated in serum. Oxidative stress in liver and kidney tissue was estimated using Thiobarbituric acid reactive substances (TBARS), glutathione (GSH) content, superoxide dismutase(SOD), and Catalase (CAT) RESULTS: CCl(4 )caused a marked rise in serum levels of ALT and AST (P < 0.05). TBARS levels were significantly increased whereas GSH, SOD and CAT levels decreased in the liver and kidney homogenates of CCl(4 )treated rats. HDN (200 mg/kg) successfully attenuated these effects of CCl(4) CONCLUSION: In conclusion, our study demonstrated a protective effect of HDN in CCl(4 )induced oxidative stress in rat liver and kidney. This protective effect of HDN can be correlated to its direct antioxidant effect.